Household Clustering of Escherichia coli Sequence Type 131 Clinical and Fecal Isolates According to Whole Genome Sequence Analysis. (16th June 2016) - Johnson, James R.; Davis, Gregg; Clabots, Connie; Johnston, Brian D.; Porter, Stephen; DebRoy, Chitrita; Pomputius, William; Ender, Peter T.; Cooperstock, Michael; Slater, Billie Savvas; Banerjee, Ritu; Miller, Sybille; et al.
Abstract : In a whole genome-based phylogeny, clinical and fecal isolates of Escherichia coli sequence type 131 ( H 30R1 and H 30Rx subclones) from six households formed household-specific clusters, interspersed among reference ST131 genomes. This supported the fecal-urethral hypothesis and confirmed within-household strain sharing. Abstract: Background.  Within-household sharing of strains from the resistance-associated H 30R1 and H 30Rx subclones of Escherichia coli sequence type 131 (ST131) has been inferred based on conventional typing data, but it has been assessed minimally using whole genome sequence (WGS) analysis. Methods.  Thirty-three clinical and fecal isolates of ST131- H 30R1 and ST131- H 30Rx, from 20 humans and pets in 6 households, underwent WGS analysis for comparison with 52 published ST131 genomes. Phylogenetic relationships were inferred using a bootstrapped maximum likelihood tree based on core genome sequence polymorphisms. Accessory traits were compared between phylogenetically similar isolates. Results.  In the WGS-based phylogeny, isolates clustered strictly by household, in clades that were distributed widely across the phylogeny, interspersed between H 30R1 and H 30Rx comparison genomes. For only 1 household did the core genome phylogeny place epidemiologically unlinked isolates together with household isolates, but even there multiple differences in accessory genome content clearly differentiated these 2 groups. The core genome phylogeny supported within-household strain sharing, fecal-urethral urinary tract infection pathogenesis (with the entire household potentially providing the fecal reservoir), and instances of host-specific microevolution. In 1 instance, the household's index strain persisted for 6 years before causing a new infection in a different household member. Conclusions.  Within-household sharing of E coli ST131 strains was confirmed extensively at the genome level, as was long-term colonization and repeated infections due to an ST131- H 30Rx strain. Future efforts toward surveillance and decolonization may need to address not just the affected patient but also other human and animal household members.